(untitled) (Journal of Dhaka National Medical College & Hospital, 2019)
Background: Diabetes mellitus (DM) is one of the important morbidity known to affect the outcome of tuberculosis (TB). The rising prevalence of DM in TB patients in endemic areas may adversely affect TB control. Speeding up the diagnostic, curative and preventive services are required to address DM. Methods: This cross-sectional observational study was conducted to determine the frequency of glucose intolerance among patients with TB attending the Medicine Department of BIRDEM General Hospital, Dhaka. Total 59 patients were selected according to eligibility criteria. Demographic data were collected from individual patient by investigator with an aid of a semi-structured questionnaire. Results of OGTT were also included during data collection of the patients. Edited and encoded data were analyzed with a computer software Statistical package software system (SPSS) version 22. Results: Total 59 cases were taken for this study. Out of which 35 (59.32%) cases were diagnosed as having pulmonary TB and rests 24 (40.78%) cases were diagnosed as having extra pulmonary tuberculosis. Mean age was found 35.8 ± 19.7 years with range from 18-65 years. Out of the 59 patients with TB, 10 (16.95 %) had glucose intolerance of which 2 (3.39%) had impaired fasting glucose (IFG), 05 (8.47 %) had impaired glucose tolerance (IGT) and 3 (5.08%) were frankly diabetes. It was observed that majority 35 (59.32%) patients belonged to 36-55 years. But the frequency of abnormal OGTT was more 3, (23.07%) out of 13 in 55-65 years age group. The number of cases of pulmonary TB decreased with increasing age and the relative number of those with glucose intolerance increased. The frequency of glucose intolerance was more in male 8, (23.52%) out of 34. But there were no significant difference in different ages and sex. Majority of patients belonged to the rural population (39, 66.10% out of 59) while most of them were of lower socioeconomic class (24 of 59). The frequency of glucose intolerance was interestingly more among the rural 08 (20.51%) and those was in the low socioeconomic class. 7, (29.17%) and 8 (41.9%) cases were employed, self-employed patients but the results were not statistically significant. Out of 59 patients, glucose intolerance was more common in pulmonary TB (7/35, 20%) cases than extra pulmonary TB (3/24, 12.5%). Glucose intolerance was more common in smear positive pulmonary TB 3/10 (30%) patients and low 4/25 (16%) in smear negative patients. On radiological findings, the most common was cavitary lesion and glucose intolerance was found in 2/4, 50% patients. Glucose intolerance was 2/10 (20%) and 1/10 (10%) who had pleural effusion and consolidation respectively. Among patients with peritoneal TB glucose intolerance was 1 (12.5%) out of 8 patients who have ascites but no glucose intolerance was found in ileo-caecal TB and on fluid study there were increased glucose intolerance in tubercular pleural effusion 2 (20%) out of 10 patients and in ascites 1 (12.5%) cases out of 8 but no glucose intolerance in CSF study and found non-significant difference. Conclusion: Glucose intolerance was 10/59 (16.95%) in patients with tuberculosis and more common in pulmonary TB patients than Extra Pulmonary TB and more in smear positive pulmonary tuberculosis patients than smear negative patients. J. Dhaka National Med. Coll. Hos. 2019; 25 (01): 43-47